(3QSGdI aj GdehGVY GdJi jchf Gdhba ajgG caQs - (3eMeO Hf eMeO Hf eMehO, CHh efUhQ GdneGoJpQjOj,J (B333 (3g` s ((3CMeO QaYJ s)
(3ChdgG (B:s
(3bGd Yde GdgOi GdEeGe CHh efUhQ GdeGJQjOi QVi Gddg Yfg ajeG dGjLhR Gdhba Ydjg Ef YQa hJYeO hhba caQ bWYkG YfO GdCFeI GdCQHYI hEf de jYQa CJe dJQcg GdJYdje s
(3BNQgG (B:s
(3hai GdENdGU hde jcf caQ Ke jHJOF dg cahkG CMO hGddg CYde hgPG eG YQafGg hGWdYfG Ydjg hGddg CYde HgPG Ch HZjQg ai SfI (B1285(3g` s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B19 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B300s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdbQGAGJ hGdJLhjOs